Lexical-Semantic Aspects of Dialects of American-English (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article analyzes the lexical-semantic features of the dialects of American English by thorough study of widespread variations of English language. Despite the fact that many scholars have carried out research on American English, the determination of the linguistic evaluation criteria of the dialects of American English, the fact that their lexical-semantic system is not sufficiently studied, which determines the necessity of this research. The results obtained can serve as a reliable basis for future researches in this field.